A new species of Halozercon (Acari: Zerconidae) from South Siberia (Russia) with additional information on Halozercon karacholana Wiśniewski et al., 1992 - Marchenko, Irina I. (Zootaxa, 2018)
Halozercon barguzin sp. nov. is described and illustrated based on female, male, deutonymph and protonymph specimens collected from soil and litter in the Khamar-Daban Range of South Baikal Region (South Siberia, Russia). Additional morphological information and illustrations of all developmental stages of of Halozercon karacholana Wiśniewski et al., 1992 are provided, with new data on its geographical distribution.